Itching in atopic dermatitis: patient- and physician-reported outcomes in the German Atopic Dermatitis registry TREATgermany - Weisshaar, Elke; Bentz, Philipp; Apfelbacher, Christian; Haufe, Eva; Heinrich, Luise; Heratizadeh, Annice; Abraham, Susanne; Harder, Inken; Kleinheinz, Andreas; Wollenberg, Andreas; Schäkel, Knut; Noack-Wiemers, Franca; et al. (Acta dermato-venereologica, 2023)
TREATgermany is an investigator-initiated prospective disease registry. It investigates physician- and patient-reported disease severity (Eczema Area and Severity Index (EASI), objective Scoring Atopic Dermatitis (oSCORAD), Investigator Global Assessment, Patient-Oriented Eczema Measure (POEM), Patient Global Assessment (PGA)), patient-reported symptoms (itch, sleep loss, depressive symptoms), therapy courses and dermatological quality of life (DLQI) in moderate-to-severe atopic dermatitis with SCORAD > 20. 1,134 atopic dermatitis patients (mean age 41.0 ± 14.7 years, 42.5% females) were enrolled by 40 German recruiting sites (dermatological clinics and practices) between June 2016 and April 2021. The current analysis focuses on itch scores obtained with a numerical rating scale (NRS)) documented for the previous 3 days prior to baseline visit. The results show that 97.2% (1,090 of 1,121) patients experienced itch. Itch severity correlated moderately with severity of atopic dermatitis oSCORAD (rho = 0.44 (0.39-0.48)) and EASI score (rho = 0.41 (0.36-0.46)). A strong correlation was found with self-reported disease severity as PGA (rho = 0.68 (0.65-0.71)), POEM sum score (rho = 0.66 (0.63-0.69)) and dermatological quality of life impairment DLQI (rho = 0.61 (0.57-0.65)). Itch as a subjective complaint is more closely correlated with patient-reported outcomes than with objective assessments by the physician.